Drivers and inhibitors of ICT adoption in Malaysian travel agencies: TOE perspective - Munikrishnan, Uma Thevi; Ng, Siew Imm; Ho, Jo Ann; Raja Yusof, Raja Nerina (Faculty of Economics and Management, Universiti Putra Malaysia, 2018)
Buhalis and Law (2008) acknowledged the synergistic interaction between technology and tourism has brought revolutionary changes on the industry structure especially among the Traditional Travel Agencies (TTA) due to the emergence of Virtual Travel Agencies and infomediaries Interestingly, though it is recognised that ICT epitomizes a strategic instrument for survival, yet TTAs are vulnerable to the growth of the ICTs as a tool for e-business and information dissemination (Khuja and Bohari, 2012). Therefore, it is crucial to investigate the factors driving and inhibiting ICT adoption among the Malaysian TTAs. Technology-Organization-Environment (TOE) framework which provides a solid theoretical basis is used to evaluate technology adoption factors. Overall, researchers have agreed with Tornatzky and Fleischer (1990) that the three aspects of TOE influences technology adoption. Qualitative multiple case studies method was used to ensure the adoption factors were explored in depth. Semi-structured interviews is used to collect data from fourteen case firms in Malaysia. The findings revealed three variable categories, namely technology, organization and environment have either driven and/or inhibited the ICT adoption among the TTAs in Malaysia. The TTAs perceived the technology attributes, organizational attributes, environmental attributes as the factors influencing the ICT adoption.